PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IX SMP NEGERI 2 TILATANG KAMANG - Putri, Ruly Harila (Jurnal Edukasi dan Penelitian Matematika, 2024)
Abstract – Learning outcomes are a very important tool for assessing academic success. High-quality outcomes are a guarantee of an effective learning process. Unfortunately, data on this in the ninth grade of SMPN 2 Tilatang Kamang is inadequate. One model that can overcome this is the Discovery Learning (DL) model. This study aims to explore how mathematics learning outcomes can develop using the DL model and to find out whether the conventional approach provides optimal results compared to the model. This study used a descriptive quasi-experimental design with a posttest-only control group that was not equal to the experimental group. The math quiz results showed that the experimental group learned more. The null hypothesis (H0) was rejected as the t-test P-value = 0.027, generated by examining the test data, was smaller than the significance level (α). This study found that DL users outperformed those who used conventional learning strategies in math.Keywords– Mathematical Learning Achievement, Conventional Learning, Discovery Learning